Acid-producing Bacteria and Yeasts Isolated from Arabica Coffee Plantations in Central Java and East Java, Indonesia - Dinihari Indah Kusumawati; Toto Iswanto; Puspita Lisdiyanti (Annales Bogorienses, 2021)
The converting process of coffee cherries to green coffee beans was conducted through the fermentation process using lactic acid bacteria (LAB) and yeasts to degrade coffee's mucilage. This present study aims to isolate acid producing bacteria and yeasts from three type of samples obtained from Arabica Coffee Plantations in Central Java and East Java, Indonesia. A total of 31 bacteria and 15 yeasts were obtained from this study. From 31 bacteria, 6 strains were identified as Lactobacillus sp. isolated from all samples; 15 strains were identified as P. pentosaceus; 4 strains as L. pseudomesenteroides; 1 strain as K. quasipneumoniae; and 5 strains as A. tropicalis from exocarp of coffee fruit. While from 15 yeast, 8 strains were identified as C. tropicalis isolated from soil; 2 strains as P. kudriavzevii from Luwak feces, and 5 strains as C. fabianii from exocarp of coffee fruit. A total of 25 strains of lactic acid bacteria can release lactic acid bacteria on MRS agar supplemented with 0.5% CaCO3, but 1 strain of K. quasipneumoniae and 5 strains of A. tropicalis produced acid weakly. Four strains of C. tropicalis showed the ability to form thin clear zone formation contrariwise with four other strains. This study adduced that waste materials and soil from the plantation coffee’s area are potential sources to obtaining acid-producing bacteria which is utilized in fermentation process of coffee cherries.